Evaluasi Pelaksanaan Pemilihan Kepala Daerah Langsung Dalam Mewujudkan Demokratisasi di Tingkat Lokal - Edah Jubaedah (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2008)
This article presents the result of the study about direct local government election process in several districts in Indonesia. Local government elections, known as Pilkada, have conducted since mid-2005, there are hundreds of regions (provinces, districts and municipalities) have conducted Pilkada, and hundreds move will do the same in the years ahead. This study finds that there are lots of problems still occur during direct local government election process. There main problems are institutional problems, preparation phase problems and implementation phase problems. Institutional problems which are still arise during the direct local election such as lack of independency and profesionalism of local government election are insufficient time for local electoral body to prepare the election process; lack of clarity about recruitment mechanism of PPK, PPS and KKPS; and lack of socialization program. Finally, problems occurs during implementation phase of pilkada are the weaknesses of data updating, problem in candidates recruitment, infringements during the campaign, lack of managementof logistics and budget accountability. This study recommends that government should reformulate the rule of direct local government election.